Unlocking Potential: Harnessing Language Learning Apps to Support Young Learners with ADHD - Al-Mutairi, Musaed A. (International Journal of Scientific Research and Management (IJSRM), 2024)
This article explores the potential of language learning applications in supporting young learners with Attention Deficit Hyperactivity Disorder (ADHD). It highlights the challenges faced by this demographic in language acquisition, such as difficulty sustaining attention, impulsivity, and hyperactivity. The article emphasizes the importance of early intervention and tailored support in fostering language development in young learners with ADHD. Language learning applications offer benefits such as customizable pacing, engaging multimedia content, instant feedback, and gamification elements. Real-life case studies demonstrate the transformative impact of these apps on the language acquisition journey. Design considerations for ADHD-friendly apps include a simplified user interface, clear instructions, visual aids, structured routines, multisensory elements, rewards, and positive reinforcement. Practical strategies for parents and educators include collaborative learning, realistic goal-setting, progress monitoring, and consistent usage routines. Success stories and testimonials highlight the real-world impact of language learning apps in supporting young learners with ADHD.